Perceptions of Third Country Migrants About Secondary Labor Market Concentration. A Case of Call Center Jobs in Romania - Roșca, Vlad I. (Calitatea Vieții, 2022)
This article sets to investigate the perceptions of migrants about call center labor in Romania. Narrative evidence was gathered from six oral history interviews conducted between June 2021 and January 2022 with third country nationals who lived in Romania. All of them had call center labor experiences in this country. Narrative research is employed in order to analyze and interpret the lived experiences recalled by the migrants. Results show that the lack of destination language skills, of sufficient professional experience and the unrecognition of home society qualifications are among the most encountered ideas which migrants believe restrict their access onto the primary labor market and force them into the secondary market. Deskilling is also common among migrants, who accept secondary labor market jobs, below their qualifications, because of migrant-related status reasons that impede their access onto the primary labor market. Nonetheless, high attrition rates specific to call center businesses can be regarded as an advantage for migrants, allowing them ease of access and exit onto and from the secondary labor market.